SECRETION OF CALCIUM IN THE SALIVA OF LONG-TERM TOBACCO USERS - Khan, Ghulam Jillani; Mehmood, Rashid; Din, Salah -ud-; Marwat, Fida Muhammad; Haq, Ihtesham -ul-; Rehman, Jamil-ur- (Journal of Ayub Medical College Abbottabad, 2005)
Background: Secretion of calcium in saliva depends upon salivary flow rates in non-tobacco users and greater is the rate, lower is the concentration and vice versa. In long-term tobacco users the taste receptors, a primary site for salivary secretion, are constantly exposed to tobacco for long time thus presumably affecting the salivary reflex. Therefore the main purpose of the study was to study the secretion of calcium in the saliva of theses individuals. Methods: Subjects of the study were divided into smokers, pan, (tobacco-betel-lime "quid") chewers, niswar (moist oral snuff) dippers and non-tobacco users as controls. Each group was comprised of 20 healthy male adults. The saliva of each subject was collected under resting condition and following application of crude nicotine and citric acid solutions to the tip of his tongue. Results: All groups of long-term tobacco users exhibited significantly higher concentrations of calcium before and after stimulation when compared with controls .However significant drop was observed in calcium levels of all groups including controls after stimulation but this drop was more pronounced after stimulation with citric acid than after stimulation with nicotine. Conclusion: We conclude that higher levels of calcium are present in the saliva of long-term tobacco users than non users which decreases as the flow of saliva increases. Key Words: Saliva, calcium, tobacco users.